2021
DOI: 10.4103/ijem.ijem_331_21
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between luteinizing hormone levels and ART outcome in GnRH antagonist protocols? A retrospective cross-sectional study

Abstract: Objective: To evaluate the potential link between serum LH concentrations on the day of oocyte triggering and pregnancy outcome during controlled ovarian hyperstimulation. Materials and Methods: In this retrospective cross-sectional study, data of women ≤42 years undergoing fresh embryo transfer cycles and who had downregulated with GnRH antagonist protocol in a 12-month period was reviewed. Patients with incomplete hospital records were excluded. Women were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, Depalo et al reported that patients with positive pregnancy test results had significantly lower LH levels at the beginning of the stimulation period and lower LHLOT [28] . Eftekhar et al found that LHLOT <1.49 may negatively affect the implantation rate rather than the clinical pregnancy rate [29] . Moreover, Merviel et al found that LHLOT >0.5 or ≤0.5 IU/L had no impact on oocyte yield and clinical pregnancy rates [17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Depalo et al reported that patients with positive pregnancy test results had significantly lower LH levels at the beginning of the stimulation period and lower LHLOT [28] . Eftekhar et al found that LHLOT <1.49 may negatively affect the implantation rate rather than the clinical pregnancy rate [29] . Moreover, Merviel et al found that LHLOT >0.5 or ≤0.5 IU/L had no impact on oocyte yield and clinical pregnancy rates [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Merviel et al [17] GnRH-A ≤0.5 >0. 5 No influence (119) (151) Benmachiche et al [18] Eftekhar et al [29] GnRH-A <1.49 [53] GnRH-a down-regulation <0.5 >0.5 LH < 0.5 IU/L increased risk of early pregnancy loss (98) (102) Balasch et al [60] GnRH-a down-regulation <1 (44) or ≤0.7 (21) or ≤0.5 (10) or >0.5 (134) No influence ≥1 (100) >0.7 (123) Humaidan et al [54] GnRH-a down-regulation <0.5 0.51-1.0…”
Section: Discussionmentioning
confidence: 99%